PENGARUH SELEKSI PEGAWAI DAN KOMPENSASI TERHADAP KINERJA PEGAWAI PADA PT. PRICOL SURYA INDONESIA - Chintya Prima Prihandini; Erliany Syaodih (LPPM Universitas Adhirajasa Reswara Sanjaya, 2022)
The population used in this study were employees of PT. Pricol Surya Indonesia-Karawang as many as 150 employees. The sample in this study were 110 respondents. The type of data in this study is Likert. The method of collecting data through a questionnaire. The research method used is a quantitative method.The results of the study to prove the influence of the organization on employee performance based on the results of the value test obtained by the calculated value of 4.504 and the effect of compensation on employee performance based on the test results obtained from this value of 9.076 with a significance value of 0.000, it can be ignored that employee selection and compensation have a significant effect. Against Employee Performance. Meanwhile, the influence of organization and compensation on employee performance based on the results of the f test obtained the calculated F value of 121,328 and the significance probability value of 0,000 and the α level of 5%. This shows that the results of the F test significance 0.000 smaller give a significance value of 0.05. This means that Employee Selection (X1) and Compensation (X2) simultaneously have a significant effect on employee performance.